tph SOSIALISASI PRODUK ELEKTROMEDIK HOME CARE DIMASA PANDEMI COVID-19 - Wike Kristianti; Ansor Ibrahim Usman; Endang Titi Amriati; Gita R indang Lestari; titus harjatmo (CV. Multi Kreasi Media, 2023)
One of the important aspects in the transmission of Covid-19 is maintaining the cleanliness of household tools and objects used in daily life to minimize the transmission of the Covid-19 virus through household appliances, so that it plays a role in preventing Covid-19 infection. Purpose of this Community Service is to introduce home care products from the Department of Electromedical Engineering that are useful in society due to the Covid-19 pandemic. The scope includes the impact of new habits that exist in society today during the Covid-19 pandemic. This activity will be carried out using the socialization method and the practice of using electromedical devices and their benefits. This community service activity was carried out using the Interprofessional Collaboration (IPC) approach which was coordinated by the Community Service team consisting of lecturers at the Poltekkes Kemenkes Jakarta II with different expertise backgrounds involving students at Poltekkes Emenkes Jakarta II. Activities carried out for 7 (seven) months. The results of the implementation of the activities show that there is an increase in knowledge points before and after education.